Effects of free fatty acid concentrations in choice white grease on growth performance and nutrient digestibility in weanling pigs - Hines, Robert H.; Cao, H.; Maloney, C.A.; Dean, D.W.; Lee, D.J.; Park, J.S.; DeRouchey, Joel M.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
As much as 53% free fatty acids in choice white grease did not adversely affect piglet performance. Thus, concentration of free fatty acids, if they are not otherwise damaged or rancid, is not an acceptable measure of fat quality.
Keywords: Swine; Weanling pigs; Fat quality; Free fatty acids